Pengaruh Biaya Produksi dan Biaya Pemasaran Terhadap Laba Perusahaan Manufaktur Subsektor Makanan dan Minuman Tahun 2017-2021 Yang Terdaftar Di Bursa Efek Indonesia (BEI) (Jurnal Kendali Akuntansi, 2023)
Profit is an increase in capital (net assets) derived from transactions that rarely occur within the company and from all transactions and other events that affect the company, except revenue (revenue) or investment owners . Study This aim For analyze Influence Cost Production And Cost Marketing to Company Profits , as well For know variable which one is the most dominant influence to profit company manufacturing sub sector food And drink . Processed data form secondary data from report annual company manufacturing sub sector food And drink the years 2017-2021 are taken in a manner in Total Smpling . Method used in study This is Panel data regression using application eviews 10 results study state that : Cost Production influential positive to profit company And Cost Marketing No influential to profit company.